Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Peningkatan Kinerja Pegawai pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Tolitoli - Emy Noviyanti; Jabal Nur; Risman Risman (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aims to determine the influence of leadership and organizational culture on improving employee performance at the Tolitoli Regency Community and Village Empowerment Service. This research uses quantitative methods. The data collection technique is using saturated samples. Data collection methods in this research are observation, interviews, questionnaires and documentation. The data analysis technique uses statistical calculations using the SPSS version 20 data processing application. Based on the t-test results in the table, it was found that leadership was 2,485 and organizational culture was 2,118. So it is concluded that the leadership variable has a calculated t value of 2.485>2.018 with a significant value of 0.017<0.05 so it can be concluded that leadership has a positive and significant effect on increasing employee performance. Meanwhile, for the Organizational Culture variable, the t-count value was 2.118>2.018 with a significant value of 0.040<0.05, so it can be concluded that the Organizational Culture variable has a positive and significant effect on improving employee performance. The f-count value obtained was 32,096>3,220 with a significant value of 0.000<0.05, so it was concluded that the Leadership and Organizational Culture variables had a positive and significant effect on improving employee performance at the Tolitoli Regency Community and Village Empowerment Service. The R square adjuster value is 0.586, which means that the contribution of the Leadership and Organizational Culture variables to improving employee performance at the Tolitoli Regency Community and Village Empowerment Service is 58.6%.